2017
DOI: 10.1186/s41239-017-0041-6
|View full text |Cite
|
Sign up to set email alerts
|

Taking social media to a university classroom: teaching and learning using Twitter and blogs

Abstract: Social media has taken many sectors including the higher education by storm. However, with wide spread fears that social media may be a distractor to pedagogy, this paper investigated how social media facilitates teaching and learning. Unlike most prior studies which relied much on soliciting mere views from students and lecturers about their intentions to use or not to use social media, this study incorporated Twitter and blogs into two undergraduate courses offered in the Department of Library and Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
172
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(199 citation statements)
references
References 26 publications
12
172
0
15
Order By: Relevance
“…This is about 62.8% of all respondents. This observation agrees with other studies which concluded that social media could comfortably facilitate the learning process for college students, if used appropriately (Chawinga 2017;Odom et al 2013;Qureshi, Raza & Whitty 2014).…”
Section: Comfortability With the Use (Ease Of Use) Of Social Media Toolssupporting
confidence: 82%
See 3 more Smart Citations
“…This is about 62.8% of all respondents. This observation agrees with other studies which concluded that social media could comfortably facilitate the learning process for college students, if used appropriately (Chawinga 2017;Odom et al 2013;Qureshi, Raza & Whitty 2014).…”
Section: Comfortability With the Use (Ease Of Use) Of Social Media Toolssupporting
confidence: 82%
“…Regardless of the negative experience that users of social media may have experienced, a well-planned use brings positive benefits to the society (Chawinga 2017;Jovanovic & Chiong 2012). One of the areas to be benefited is the learning process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, learners report that its use is beneficial because of increased connectedness with other learners meaning that they are less reliant on the lecturer, indicative of Twitter supporting independent learning (Chawinga 2017;Dhir et al 2013). Secondly, it allows learners to participate effectively in course discussion (Chawinga 2017) by creating i) continuous and transparent communication between practitioners and learners ii) information learning and communication iii) social and transparent group work, and iv) a space for learners to express views without restriction (Dhir et al 2013). Thirdly, and similar to forums, Twitter results in rapid responses (Chawinga 2017;Ricoy and Feliz 2016).…”
mentioning
confidence: 99%